Fujiko Nakaya's fog performance and embodied 'nature'. Issue 2 (4th May 2019) - Sone, Yuji
ABSTRACT: This essay discusses Fujiko Nakaya, a Japanese artist who has been known since 1970 for the use of fog in her site-specific installations. Nakaya's outdoor work is designed for and interacts with a particular site, facilitating spectators' kinaesthetic awareness through a dynamic visibility and strategies of immersion. This essay discusses Nakaya's fog work as reflecting her early contact with Western art in the late 1960s and early 1970s, filtered through a particularly Japanese aesthetic. I argue that the underlying principle informing Nakaya's fog art is one of an imagined natural core that is accessible to the spectator paradoxically through the very artificiality of the environment Nakaya creates, and through the work's facilitation of a reflexive receptiveness of one's own transience. Nakaya's work sustains an irresolvable relation between nature and culture that rejects the simple dichotomy of the human and the natural. Nakaya's work accentuates the embodied experience of the spectator, giving rise to a new form of participation and ecological awareness.